2018
DOI: 10.4097/kja.d.18.00011
|View full text |Cite
|
Sign up to set email alerts
|

Aprepitant in combination with palonosetron for the prevention of postoperative nausea and vomiting in female patients using intravenous patient-controlled analgesia

Abstract: BackgroundThe aim of this study was to evaluate aprepitant in combination with palonosetron as compared to palonosetron alone for the prevention of postoperative nausea and vomiting (PONV) in female patients receiving fentanyl- based intravenous patient-controlled analgesia (IV-PCA).MethodsIn this randomized single-blinded study, 100 female patients scheduled for elective surgery under general anesthesia were randomized to two groups: Group AP (80 mg aprepitant plus 0.075 mg palonosetron, n = 50) and Group P (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
0
22
1
Order By: Relevance
“…In contrast, in a previous study we reported a reduced incidence of PONV with the combination of ondansetron and aprepitant in patients undergoing laparoscopic surgery ( 15 ). Although we did not find a beneficial effect on the association of palonosetron and aprepitant in the present work, the incidence of PONV was lower than that reported in other studies ( 16 ), with a very low incidence of vomiting, similar to Yoo et al ( 17 ).…”
Section: Discussioncontrasting
confidence: 55%
“…In contrast, in a previous study we reported a reduced incidence of PONV with the combination of ondansetron and aprepitant in patients undergoing laparoscopic surgery ( 15 ). Although we did not find a beneficial effect on the association of palonosetron and aprepitant in the present work, the incidence of PONV was lower than that reported in other studies ( 16 ), with a very low incidence of vomiting, similar to Yoo et al ( 17 ).…”
Section: Discussioncontrasting
confidence: 55%
“…The NK-1 receptor antagonist aprepitant appears to be more effective in decreasing PONV as compared with ondansetron 189 , 190 . Aprepitant alone or in combination was associated with a low overall incidence of PONV 191 , 192 in patients undergoing laparoscopic surgery 193 , craniotomy 194 , mastectomy and thyroidectomy 195 , and elective surgery 196 and in pediatric patients 197 . Because of its high cost, aprepitant should be used only in patients at high risk of developing PONV and in those who could experience serious adverse outcomes due to PONV as well as in patients who may have side effects from less-expensive antiemetic drugs 191 , 192 .…”
Section: Perioperative Antiemetic Drugs Used For the Treatment And/ormentioning
confidence: 99%
“…On the other hand, Yoo et al 69 conducted a clinical trial of 100 moderate risk female patients undergoing moderate-to-high risk surgeries, and reported that aprepitant plus palonosetron did not significantly reduce the incidence of PONV or the rescue anti-emetic requirement when compared to palonosetron alone. One possible explanation is that, as palonosetron is intrinsically more effective than the other 5-HT 3 antagonists, the marginal gain of adding aprepitant is diminished.…”
Section: Novel Chemoprophylaxismentioning
confidence: 99%